Towards a Buen Vivir-centric Design: Decolonising Artisanal Design With Mayan Weavers From the Highlands of Chiapas, Mexico - Albarrán González, Diana (Auckland University of Technology, 2020)
The highlands of Chiapas is a Mayan region in southeast Mexico recognised for its richness in artisanal textiles. The intervention of hegemonic design in textile traditions has been used as a developmental strategy, following market-driven approaches in a field known as “diseño artesanal” (artisanal design). However, the role of artisans as producers of designers’ creations, the lack of reference to the cultural context, the unequal relationships of power, and the colonisation of Indigenous knowledge is a critical concern. This research aims to contribute to the decolonisation of artisanal design through Buen Vivir (good living, collective well-being), and the recognition of Indigenous design. At the same time, it challenges inequalities in the Mexican context with those in the conventional design field. In a similar manner to the concept of to Buen Vivir, Lekil Kuxlejal (a fair and dignified life) from the Mayan Tsotsil and Tseltal people, is explored through visual-digital-sensorial ethnography and co-design alongside Mayan weavers whose work demonstrates alternatives to textile artisanal design from a community perspective. The wider project seeks to develop a foundation for a context-based, non-Western/Indigenous design from the Global South. The study is rooted in jolobil, an ancient precolonial textile tradition known as backstrap loom weaving. Using jolobil as a research metaphor and methodology, a yosotros approach (Yo+Nosotros) weaves embodiment, sentipensar (feeling-thinking or sensing-thinking), and corazonar (reasoning and feeling with the heart) with decolonial theory, design research and co-design from the Global South. Further, drawing on Indigenous epistemologies and ontologies such as Buen Vivir and Zapatismo the study proffers a new approach to textiles as resistance, based on Mayan cosmovisión (vision of the cosmos), contributing to the collective well-being of artisanal communities. As a result, a central proposal of this study is a Buen Vivir-centric design model, the guiding principle for ethical and fair collaboration which, above all else, respects the autonomía of the community towards Lekil Kuxlejal.
Keywords: Design; Buen Vivir; Decolonisation; Textiles